Diet Variability and Stable Isotope Analyses: Looking for Variables Within the Late Neolithic and Iron Age Human Groups from Gougenheim Site and Surrounding Areas (Alsace, France). (27th February 2014) - Goude, G.; Balasescu, A.; Réveillas, H.; Thomas, Y.; Lefranc, P.
Abstract: Several human groups (from the Neolithic to the Bronze Age) have been analysed in France during the past decade (mainly for C and N stable isotope) as part of research programmes focusing on prehistoric dietary variability. The environment, cultural/social choices or even biological characteristics are among the parameters influencing food acquisition and consumption. This short report presents the first diachronic isotopic results on the palaeodiet in northeastern France. Because of the exceptional archaeological characteristics (human deposits in various positions in pits) of the bone collection from the site of Gougenheim and the surrounding areas (Late Neolithic‐Iron Age, Alsace, France), this assemblage provides a new isotopic dataset to study diet and the potential relationship with social elements or other factors involved in food choices. In order to obtain individual palaeodietary information, carbon and nitrogen stable isotope analyses were performed on 23 adults and 20 immature human bone collagen samples as well as on 25 animal remains. Data were then combined with zooarchaeological and anthropological/archaeological results to reconstruct part of the dietary pattern (i.e. protein consumed) and to detect possible links between the deposit and individual or group social status, defined here by specific mortuary practices. For the Late Neolithic period, isotopic values show, among other things, a wide δ 13 C range within the female human group, which is statistically lower than the male one. Women probably consumed more diversified food sources, suggesting increased residential mobility. Although body deposits point to the presence of two distinct subgroups, no relationship with animal protein intake was identified. Moreover, the comparison with Iron Age individuals brought to light different dietary patterns between the two periods, indicating that stable isotope values were affected throughout time either by increased millet/legume consumption or environmental/anthropic changes. Copyright © 2014 John Wiley & Sons, Ltd.